Accounting as an Administrative Aid - McKinsey, J. O. (Journal of Political Economy, 1919)
Business administration is largely a matter of control-control and direction of the various factors involved in the conduct of a business enterprise. The basis of control is information. In fact, business control, and hence scientific administration, may be said to consist of the proper application of information correctly interpreted. Business methods and practices are changing so rapidly, new problems are arising so frequently, and conditions vary so widely in different localities and different lines of business that set rules for the administration of a business cannot be established. It is true that there are certain general principles which may be regarded as more or less universally applicable, but their particular application in each specific case must be influenced by current information in regard to the factors involved. It is, of course, untrue to assume that the business executive is not influenced by precedent or that his acts are governed entirely by present expediency, but it is important to realize that he is continually revising his past conclusions and policies in the light of present information-information in regard to the past and information in regard to the probable future. When business organization was simple and the business enterprise small and its activities local, the owner, who was also the manager, was able to obtain without assistance the necessary information upon which to base the conduct of his business. This is still true in some cases, for instance, the village storekeeper. He may keep his accounting records, plan his sales campaign, determine the extent and nature of the advertising to be done, select the goods to be purchased, secure the necessary funds from sources which he chooses, and actively direct, if not actually perform, all the executive operations of his business. He is able 'The writer is indebted for certain parts of the subject-matter of this article to his colleagues Mr. George E. Frazer and Mr. A. C. Hodge.